Hana's Suitcase - Levine, Karen (Albert Whitman & Company, 2003)
A biography of a Czech girl who died in the Holocaust, told in alternating chapters with an account of how the curator of a Japanese Holocaust center learned about her life after Hana's suitcase was sent to her.
Keywords: Juvenile Non-Fiction / Biographies